Crimes, harms, and wrongs: on the principles of criminalisation - Simester, A. P. (Hart Publ., 2011)
"When should we make use of the criminal law? Suppose that a responsible legislature seeks to enact a morally justifiable range of criminal prohibitions. What criteria should it apply when deciding whether to proscribe conduct? Crimes, Harms, and Wrongs is a philosophical analysis of the nature, significance, and ethical limits of criminalisation. The authors explore the scope and moral boundaries of harm-based prohibitions, proscriptions of offensive behaviour, and 'paternalistic' prohibitions aimed at preventing self-harm. Their aim is to develop guiding principles for these various grounds of state prohibition, including an analysis of the constraints and mediating factors that weigh for and against criminalisation. Both authors have written extensively in the field. In Crimes, Harms, and Wrongs they have reworked a number of well-known essays and added several important new essays to produce an integrated, accessible, philosophically-sophisticated account that will be of great interest to legal academics, philosophers, and advanced students alike"--Provided by publisher